The Role of Local Sago Food in Realizing Food Security of Sago Farmers in Lasolo District North Konawe Regency in the Covid-19 Pandemic - Fitriani Fitriani; Muhammad Aswar Limi; Samsul Alam Fyka (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
This study seeks to determine the food security status of sago farmers in Lasolo District, North Konawe Regency, during the Covid-19 pandemic, as well as the function of Sago in achieving food security for sago farmers in Lasolo District, North Konawe Regency, during the Covid-19 pandemic. From August to September 2021, this research was conducted in Lasolo District, North Konawe Regency. This study's population consisted of 20 sago producers. Using the census technique, the researchers sampled the entire population of sago producers in the Lasolo District. The household food security survey instrument developed by the United States Department of Agriculture (USDA) was utilized for this study's analysis. The results indicated that 50% of sago producers in the Lasolo District had a marginal food security status, 30% had a low food security status, and 30% were deficient. At the same time, there were no food-secure households—high-calorie foods. Upon categorization into two categories, each sago farmer falls at the 50 percentile for food security and food insecurity. The previous year, sago producers in the Lasolo District consumed Sago as a staple diet. In the past week, 80 percent of Sago local foods were finished with a frequency of three to four days. This demonstrates that Sago plays a crucial role in ensuring the food security of sago producers in the Lasolo District, particularly those who are food insecure.